PGC-1α regulates critical period onset/closure, mediating cortical plasticity - Zhang, Wei-Jun; Shi, Hou-Zhen; Guo, Mei-Na; Xu, Long-Fei; Zhai, Hong-Ru; Liu, Zi-Zhong; Zhu, Yong-Qiang; Zhang, Wei-Ning; Wang, Jia (Frontiers in Molecular Neuroscience, 2023)
Peroxisome proliferator activated receptor PPAR coactivator-(PGC-1 ) is concentrated in inhibitory interneurons and plays a vital role in neuropsychiatric diseases. We previously reported GABAergic neuron-specific Pgc-1alpha knockout (KO) mice (Dlx5/6-Cre: Pgc-1alpha f/f ) presented some characteristic features of schizophrenia (SZ). However, there is a fundamental gap of the molecular mechanism by which Pgc-1alpha gene involved in the neurobehavioral abnormalities of SZ. Loss of critical period (CP) triggers-maturations of parvalbumin interneurons (PVIs) and brakes-formation of perineuronal nets (PNNs) implicates mistimed trajectories during adult brain development. Here, using the Pgc-1alpha KO mouse line, we investigated the effect of PGC-1 on developmental trajectories to SZ and confirmed Pgc-1alpha gene deletion resulted a failure of CP onset and closure, therefore prolonged cortical plasticity timing. PNN development and maintenance is necessary for regulating PVI function and closing CP plasticity window, a manipulation of PNN structure is a potential way to alter neuronal plasticity. For this to be practicable, GM6001, a broad-spectrum matrix metalloproteinase (MMP)-inhibitor was applied and we confirmed the treatment could effectively corrected CP plasticity window and meliorated synaptic ultrastructure in Pgc-1alpha KO brain. Besides, the intervention effect on neuronal plasticity was followed by rescuing short-term habituation deficits and aberrant salience, some characteristic features of SZ. Taken collectively, these findings suggest that the role of PGC-1 in regulating cortical plasticity is mediated, at least partially through regulating critical period onset/closure. Strategically-introduced reinforcement of molecular brakes may be a novel preventive therapy for psychiatric disorders associated with PGC-1 dysregulation.